Recent Advances in Investigating Functional Dynamics of Chromatin - Shi, Xiangyan; Zhai, Ziwei; Chen, Yinglu; Li, Jindi; Nordenskiöld, Lars (Frontiers in Genetics, 2022)
Dynamics spanning the picosecond-minute time domain and the atomic-subcellular spatial window have been observed for chromatin in vitro and in vivo. The condensed organization of chromatin in eukaryotic cells prevents regulatory factors from accessing genomic DNA, which requires dynamic stabilization and destabilization of structure to initiate down-stream DNA activities. Those processes are achieved through altering conformational and dynamic properties of nucleosomes and nucleosome-protein complexes, of which delineating the atomistic pictures is essential to understand the mechanisms of chromatin regulation. In this review, we summarize recent progress in determining chromatin dynamics and their modulations by a number of factors including post-translational modifications (PTMs), incorporation of histone variants, and binding of effector proteins. We focus on experimental observations obtained by high-resolution techniques, primarily including nuclear magnetic resonance (NMR) spectroscopy, Förster (or fluorescence) resonance energy transfer (FRET) microscopy, and molecular dynamics (MD) simulations, and discuss the elucidated dynamics in the context of functional response and relevance.